2019
DOI: 10.4314/tjpr.v18i2.25
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of celecoxib and glucosamine sulfate on inflammatory factors and oxidative stress indicators in patients with knee osteoarthritis

Abstract: Purpose: To investigate the combined effect of celecoxib and glucosamine sulfate on inflammatory factors and oxidative stress indicators in patients with knee osteoarthritis (KOA). Methods: Patients were randomly assigned to two groups of 60 patients each: control group and study group. The control group received celecoxib at a dose of 200 mg/kg/day, while the study group received glucosamine sulfate (500 mg/kg) in addition to celecoxib, thrice a day. Treatment in both groups lasted 8 weeks. The serum levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
(5 reference statements)
1
4
0
Order By: Relevance
“…A number of clinical studies reported that the combination of celecoxib and GS effectively modulate immune inflammatory response, oxidative stress damage, and joint pain and function in patients with knee OA [70][71][72]. Our results demonstrate, for the first time, the synergistic effect of celecoxib and GS on human OA chondrocyte metabolism.…”
Section: Discussionsupporting
confidence: 52%
“…A number of clinical studies reported that the combination of celecoxib and GS effectively modulate immune inflammatory response, oxidative stress damage, and joint pain and function in patients with knee OA [70][71][72]. Our results demonstrate, for the first time, the synergistic effect of celecoxib and GS on human OA chondrocyte metabolism.…”
Section: Discussionsupporting
confidence: 52%
“…This study showed that the combination of pCGS and celecoxib significantly reduced the levels of inflammatory and oxidative stress parameters and markedly lowered pain scores. This supports a possible synergistic role in inhibiting the progression of OA and improving joint function [33]. An RCT conducted by Sun and colleagues compared the use of pCGS and etoricoxib versus etoricoxib alone.…”
Section: Synergistic Effect Of Nsaids and Symptomatic Slow-acting Dru...mentioning
confidence: 81%
“…Two randomized controlled trials (RCTs) were designed to evaluate the reparative effects of combination therapy with pCGS and NSAIDs in patients with knee OA. In the study by Gang and colleagues, 120 patients with knee OA were randomized to two groups, with the intervention group treated with a combination of pCGS (a total of 1500 mg/day) and celecoxib (200 mg/day), while the control group received celecoxib alone (200 mg/day) [ 33 ]. This study showed that the combination of pCGS and celecoxib significantly reduced the levels of inflammatory and oxidative stress parameters and markedly lowered pain scores.…”
Section: Synergistic Effect Of Nsaids and Symptomatic Slow-acting Dru...mentioning
confidence: 99%
“…In an RCT including elderly people with temporomandibular joint OA, treatment with an intra-articular hyaluronic acid injection in combination with glucosamine hydrochloride (oral 720 mg for 3 months) was shown to be greatly beneficial by further reducing the IL-6, IL-1β, and TGF-β levels if compared with people treated with only hyaluronic acid injection [ 55 ]. Glucosamine sulphate (1500 mg/day) in addition with celecoxib (200 mg/day) supplemented in patients with knee OA for 8 weeks showed a better redox status expressed as higher serum SOD activity and lower serum MDA levels compared with the control group (celecoxib alone) [ 56 ].…”
Section: Nutraceuticals Used For the Prevention Of Worsening And Management Of Oamentioning
confidence: 99%